2012
DOI: 10.1556/jba.1.2012.2.3
|View full text |Cite
|
Sign up to set email alerts
|

The experience of pregnancy in women with a history of anorexia nervosa: An interpretive phenomenological analysis

Abstract: Background and aims:To explore the experience of pregnancy for women who have a history of anorexia nervosa (AN), in relation to the impact of AN on pregnancy, and pregnancy on AN. Methods: Semi-structured interviews were conducted with six women with a history of AN. Data were analysed using Interpretive Phenomenological Analysis. Results: Four super-ordinate themes emerged: 'Effortful resistance of AN'; 'The unvalued self, valued other dialectic'; 'In new territory'; and 'Feeling distanced'. Conclusions: Var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In a paper from Bailey (1999), the participants talk recurrently about the 'unreality' of the experience, and the fact that they had to look constantly at their body to be reminded about the changes that were about to take place. For women with ED, this experience can be particularly disruptive; on the one hand, they feel uncomfortable with changes in their body, and on the other, they are not yet identified with the mother-to-be (Mason et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a paper from Bailey (1999), the participants talk recurrently about the 'unreality' of the experience, and the fact that they had to look constantly at their body to be reminded about the changes that were about to take place. For women with ED, this experience can be particularly disruptive; on the one hand, they feel uncomfortable with changes in their body, and on the other, they are not yet identified with the mother-to-be (Mason et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Tierney, Fox, Butterfield, Stringer, and Furber (2011) described how women with ED seem to be caught between opposite loyalties (between their ED and the future baby's demands) during pregnancy. A study of women with AN (Mason, Cooper, & Turner, 2012) highlighted the theme of 'new meaning of embodiment', which the authors define as a difficulty in adapting to a new status and the emergence of a new relationship with the body during pregnancy. Other studies have focused on one particular aspect of motherhood, such as the post-partum period (Patel, Lee, Wheatcroft, Barnes, & Stein, 2005) and found that women with ED reported being highly distressed by the intensity of body and shape concerns, or breastfeeding (Stapleton, Fielder, & Kirkham, 2008).…”
Section: Qualitative Studies On Pregnancy and Edsmentioning
confidence: 99%
“…Women with eating disorders are often reluctant to disclose their illness to healthcare professionals (Freizinger, Franko, Dacey, Okun, & Domar, ; Morgan et al, ), which may be due both to a fear of stigma (Mason, Cooper, & Turner, ) or fear that services might respond in a negative way to the disclosure. Many women with eating disorders therefore go undetected and untreated during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Two case reports and two case series found that the behaviour symptoms (such as purging behaviour, restrictive eating and the use of laxatives) related to disordered eating in the woman with AN were worsened during pregnancy [ 29 32 ]. One case report found the opposite, where the patient had reduction of behaviour symptoms during pregnancy, but emotional and cognitive symptoms persisted [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Increased hyperemesis was mentioned by one cohort study and one case study [ 23 , 33 ]. As pre-pregnancy rate of vomiting behaviour was not reported, it is uncertain if the finding of the studies could be attributed to purging behaviour from AN.…”
Section: Discussionmentioning
confidence: 99%